Preparation and characterization of novel chiral metasurfaces and their interaction with active materials - Wang, Zeng (2018)
Chirality is essential for lives. It is built in numerous crucial bio-molecules to rule their interactions. However, the natural existing chirality is mostly extremely weak that thus highly obstructs the detection and investigation of it. In order to address this problem, artificial stereoscopic chiral nanostructures, also named 3D chiral metamaterials have been proposed and showed huge chiral responses. In contrast to the 3D chiral metamaterials, novel chiral metasurfaces manifest obvious superiorities in terms of liable fabrication and ultra-compact integration, while there is still a distance away from the ideal. One problem is that the chiral responses from the chiral metasurfaces are relatively weak, and moreover, the lack of design methodology of the chiral metamolecules also hinders the improvements. Another is the tunability of the chiral responses. Due to the complexity of the chiral structures, it is challenging to achieve tunable optical chiral responses that only based on the localized surface plasmon resonances via simply altering the parameters, which highly limits the practical usage. This thesis endeavors to provide solutions of more versatile and advanced chiral metasurfaces possessing much enhanced and controllable optical chiral responses. In further, via introducing propagating mode and apexes in chiral metasurfaces, deeper physical understandings of their chiral responses are also achieved. Furthermore, thanks to the achieved tailored chiral responses, the direct CPL emission is obtained via coupling the chiral metasurface with QDs. Nowadays, CPL has been widely used in chemical and biological industries, however its generation still relies on the conversion from linear polarized light, which not only requires expensive waveplate setup, but also bring in energy lose during the process. Therefore, the hybrid system demonstrated in this thesis for directly CPL emission is very significant for providing a feasible way to address these problems and shed light for the future studies.